Komunikasi Formal dan Informal Dalam Jaringan Komunikasi - Mala Ulfiyah; Siti Saripah; Encep Syarifudin (Departement of Mathematics Education, 2023)
There is no denying the necessity of communication for humans. Comunication allows people to interact with one another in daily life, at work, relationships, in society, and wherever they are. The success of an organization can be ensured through effective organizational communication. An organization must have effective communication. We can establish and maintain friendship, understand each other, share knowledge, uphold civilization, and achieve common goals through communication. However, poor communication can also result in fights, animosities, advances, and the pursuit of ideas, all of which prevent us from achieving our goals. Leaders and team members should therefore be aware of, understand, and practice their communication skills.